Microbiological safety of commonly available eye ointments and their in-vitro anti-bacterial potency (Bangladesh Journal of Microbiology, 2019)
Current study attempted to check out the microbiological quality of some common sterile ointment commonly implemented for the treatment of eye infections in Bangladesh. Seventeen (17) different eye ointment (T-Mycin, Aprocin, Bactin, Optimox and Cloram, Hypomer gel, Sonexa, Polytracin, Cero, Aristobet, Lotepred, Herpigel, Gentob, Xoviral, Zirgan, Xovir, Tomycin, Tobirax, AFm-plus and Parafresh) were microbiologically examined through common and traditional cultural methods. Total viable bacterial and fungal contamination was found up to 106 and 105 cfu/ml respectively. Among the 17 samples T-Mycin, Aprocin, Sonexa, Polytracinand Tomycinwere free from fungal contamination. All the samples significantly exceeded United States Pharmacopeia (USP) or British Pharmacopeia (BP) limit (